The debate of Water Fluoridation - Elhejazi, Zainab (Libyan Journal of Dentistry, 2021)
Background: This study was aimed to survey clinicians in Libya for their routine approach of dental implant maintenance and to determine if a ‎relationship exists between the formal undergraduate education and their previous ‎attendance and interest in future implant related continuing education courses.‎ Methods: A survey of 35–questions ‎specifically developed for this study was distributed to all implant clinicians attending a ‎national continuing education course that was held in Tripoli on June/29/2018. All items ‎on the survey reflected content found in publications that had addressed maintenance of ‎dental implants.‎ Participants voluntarily completed and submitted their questions survey to the ‎corresponding author before the end of the course.‎ Results: Targeting 60 participants, the response rate was 63.33% (n=38).‎ Four (10.5%) reported that they have practiced for over 15 years, while‏ ‏Nine (23.6%) ‎have practiced 11 to 15 years.‎‏ ‏‎ Fourteen (36.8%) have practiced 5 to 10 years and‎‏ ‏Eleven ‎‎(28.9%) have practiced 5 years or less. Fourteen (36.8%) reported that they have not ‎received training in class room and clinic on implant care while attending dental school. 5 ‎‎(13.1%) have not participated in any continuing education course on implant maintenance ‎after school graduation. The majority (94.7%) of the implant clinicians expressed interest ‎in continuing education courses to strengthen backgrounds in maintenance of dental ‎implants.‎ Conclusions: Results indicated that additional knowledge need to be gained regarding ‎dental implant care in order to guide patients’ confidence toward the optimal most ‎successful teeth replacement option. Furthermore, a well-established structured academic ‎program might be necessary to teach implant maintenance at undergraduate and ‎postgraduate levels both theoretically and practically.‎